Burglary Expertise: Comparing Burglars to Other Offenders. Issue 2 (1st February 2017) - Roth, Jeffrey J.; Trecki, Vanessa L.
ABSTRACT: Researchers have studied offense-specific expertise among burglars with a variety of methods, including by comparing their simulated target choices to those of students, residents, and police officers. However, prior work has almost never compared the choices of burglars and non-burglar offenders, and so it is unclear whether burglars' expertise exceeds that possessed by others with similar backgrounds and lifestyles. The present study adds to this literature by using a series of home photographs to compare the choices of burglars and non-burglar offenders. In the analysis, although similar factors influenced the choices of both groups, hints of expertise did emerge.